Tingkat Penerapan Manajemen Mutu pada UMKM Pembenihan Udang di Jawa Timur - Wisriati Lasima; Muhammad Syamsun; Darwin Kadarisman (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2012)
Shrimp is one of the leading commodities of the fisheries. Quality seed is one of the critical success factors of the cultivation so that the business activities of hatchery hatcheries should adopt the technique in accordance with the Indonesian National Standard (SNI) and Standard Operating Procedures (SOPs) and apply a quality management of seed of the Good Fish Breeding mode (CPIB) or Good Hatchery Practices (GHP). The aim of this thesis include (1) knowing the level of implementation of quality management in small to medium (SME’s) shrimp hatchery in and (2) analyze the relationship between the level of implementation of quality management on firm performance. Location of the research conducted on shrimp hatchery units located in the districts of Situbondo and Banyuwangi, both who have or have not passed the certification mode of CPIB. Data collection methods include interviews and observation. Level of implementation of quality management in shrimp hatcheries in both East Java that has been certified or not, is at a fairly high level, at three different levels, namely level of Quality Control (QC) Statistics (42.9%), Quality Assurance or QA (21.4%) and 35.7% at the level of implementation of Total Quality Management (TQM). From all levels of implementation of SQC quality management, QA and TQM, there are four predominant factors that could affect the company's performance, namely: cost efficiency, the percentage of undergraduate (S1), human resource (HR) Percentage training per year and the percentage of customer complaints. Policies need to be taken to the level of TQM is to conduct QC management so that the dominant factors that can provide high business performance can be maintained, to the level of SQC is to conduct QC activities are synchronized with the training activities is appropriate, considering the level of training at this level relatively very low. While the policy needed to be taken to the level of QA is the need to improve the quality fry strived to meet the established minimum standards and will be even better if the feasibility of obtaining certification so it will be able to improve the competitiveness of selling fries, both quantity and price. A guaranteed quality of production need to be given this level has a number of customer complaints is very high compared to the two other levels, well above average